The Influence of Socio-Economic Factors on The Productivity of Farmers in The Business of Layers in Blitar Regency - Dwiki Alfikriyadi Lutfi; Sumarji Sumarji; Ahsin Daroni (ANIMAL PRODUCTION, 2020)
Blitar District is one of the areas that has potential in developing laying hens. However, laying hens in Blitar are still traditionally carried out and have not paid attention to aspects of effectiveness and efficiency economically. The purpose of the study was to find out the profile of farmer , test the level of farmer productivity and examine the effect of socio-economic factors (the age of farmer, education level, length of livestock raising and number of livestock) on labor productivity in laying hens in Blitar District. The study used a survey method with a sample of 22 sub-districts in Blitar District. The determination of the number of sub-districts was chosen using the purposive sampling method, so that 6 sub-districts were selected. Respondents were selected by the quota sampling method of 10 farmer in each selected region. Data collected were analyzed descriptively and statistically. To find out the social influence on productivity, classical assumption was tested and multiple linear regression tests. Based on the results of the study, the profile of laying hens in Blitar District carried out traditional farming systems with livestock ownership including high categories that had heterogeneous socio-economic status. Furthermore, labor productivity of laying hens in Blitar District is quite effective and efficient, because the value is greater than the minimum wage (UMR) of Blitar District. Age of farmers, education of farmers, and number of livestock have a significant influence on the productivity of laying hens farmers in Blitar District.